Multiplying out the equation (x + 2)(4x - 3) and arranging in descending powers order gives us the quadratic form as; 4x² + 5x - 6
<h3>How to expand quadratic equations?</h3>
We want to expand the quadratic equation given as;
(x + 2)(4x - 3)
Multiplying out gives us;
4x² + 8x - 3x - 6
⇒ 4x² + 5x - 6
Thus, we can conclude that multiplying out the equation (x + 2)(4x - 3) and arranging in descending powers order gives us the quadratic form as; 4x² + 5x - 6
Read more about Quadratic equations at; brainly.com/question/1214333
#SPJ1
<span>Y = 2x + 4
16x + 4y = 40
substitute </span>Y = 2x + 4 into <span>16x + 4y = 40
</span><span>16x + 4y = 40
</span>16x + 4(2x + 4) = 40
16x + 8x + 16 = 40
24x = 40 - 16
24x = 24
x = 1
Y = 2x + 4
Y = 2(1) + 4
Y = 6
answer (1, 6)
4/5=0.8
1/50=0.02
Hope that helps
Answer:
Step-by-step explanation:
Michael is using a number line to evaluate the expression -8 - 3. After locating -8 on the number line , Michael could rewrite the expression as -8 + -3 and move 3 spaces to the left.
Answer:
2.7
Step-by-step explanation:
3% × 90 =
(3 ÷ 100) × 90 =
(3 × 90) ÷ 100 =
270 ÷ 100 = 2.7